1981
DOI: 10.1111/j.1360-0443.1981.tb03241.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Smoking History Amongst Survivors of Myocardial Infarction

Abstract: and ConclusionsOne hundred and seventeen survivors of a first attack of acute coronary heart disease had blood carboxyhaemoglobin levels checked and smoking histories recorded. All were participants in a longterm follow-up and secondary prevention programme. At last follow-up, four to eighteenyears after the initial attack, 35 stated that they were still smoking, 57 claimed to be ex-smokers, 6 were non -smokers and 19 were pipe or cigar smokers.Thirty-one of the 35 current smokers had a COHb concentration whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Smoking habits were assessed by self-reports in this study, but good correspondence with proxy information was obtained in a subsample. Other studies from medical-care settings have also reported high agreement between self-reports and objective methods in assessment of smoking (Aberg et al, 1983;Petti, Friedman, & Kahn, 1981;Ronan, Ruane, Graham, Hickey, & Mulcahy, 1981;Scott & Lamparski, 1985). However, it cannot be excluded that the reported rate of quitting may be somewhat exaggerated.…”
Section: Discussionmentioning
confidence: 96%
“…Smoking habits were assessed by self-reports in this study, but good correspondence with proxy information was obtained in a subsample. Other studies from medical-care settings have also reported high agreement between self-reports and objective methods in assessment of smoking (Aberg et al, 1983;Petti, Friedman, & Kahn, 1981;Ronan, Ruane, Graham, Hickey, & Mulcahy, 1981;Scott & Lamparski, 1985). However, it cannot be excluded that the reported rate of quitting may be somewhat exaggerated.…”
Section: Discussionmentioning
confidence: 96%
“…If these 4 samples were combined with the preceding 12 samples, the average rate would increase to 12.09%. Eight samples from five studies were classified as high risk/medical patient samples (Li et al, 1984 [two samples]; Research Committee of the British Thoracic Society, 1983 [two samples]; Ronan, Ruane, Graham, Hickey, & Mulcahy, 1981; Sillett, Wilson, Malcolm, & Bal, 1978 [two samples]; Vogt, Selvin, Widdowson, & Hulley, 1977). The average rate of false negatives was 18.34%.…”
Section: Issues Relating To the Use Of Biochemical Validationmentioning
confidence: 99%
“…. Close monitoring intervals and improving rapport between investigators and participants may help in reducing concealment(43).…”
Section: Discussionmentioning
confidence: 99%